1977
DOI: 10.1080/00018737700101393
|View full text |Cite
|
Sign up to set email alerts
|

Scattering theory of defects in crystals

Abstract: The theory of scattering is applied here to the problem of the electronic states of impurities. The S, T and K matrices, the Lippman-Schwinger and Dyson equations are used to formulate the problem. The standard concepts, methods and results of scattering theory applied to impurities discussed include the scattering amplitude, the Fredholm determinant, dispersion relations, Regge poles, Levinson's theorem and Fadeev's equations. Physical consequences considered are the change in density of states, eigenstates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 171 publications
0
5
0
Order By: Relevance
“…The pictorial representation of tunnelling spin exchange due to Kouwenhoven and Glazman (2001) is useful here, illustrated in figure 23. A description in terms of scattering is given by Rennie (1977) and a comprehensive account is to be found in the book by Hewson (1993). The expectations for magnetic properties are illustrated in figure 24.…”
Section: Knight Shifts Korringa Relaxation and Kondo Impuritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pictorial representation of tunnelling spin exchange due to Kouwenhoven and Glazman (2001) is useful here, illustrated in figure 23. A description in terms of scattering is given by Rennie (1977) and a comprehensive account is to be found in the book by Hewson (1993). The expectations for magnetic properties are illustrated in figure 24.…”
Section: Knight Shifts Korringa Relaxation and Kondo Impuritiesmentioning
confidence: 99%
“…It is another example of the perennial question as to when a strongly perturbing point defect that destroys periodicity can usefully be described within a band structure framework. The discussions of screening in terms of electron scattering by Rennie (1977), Stoneham (1975) and Alducin et al (2003) are also valuable here: whereas effective mass theory is good for long range or gradual potentials, scattering theory is better for fierce short range potentials. Rennie notes that the Yukawa potential neglects some longer range terms but has the virtue of being soluble.…”
Section: The Question Of Screening Versus Bindingmentioning
confidence: 99%
“…are not taken into consider ation. A detailed review of the state of the theory and experimental data on the electronic structure of indi vidual defects in solids can be found elsewhere [1,5,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: The Limit Of Low Impurity Concentrationsmentioning
confidence: 99%
“…Thus, calculation of the averaged Green's function is reduced to the calculation of averages of the type (23) and to summation of the series on the right hand side of formula (22). Determination of averages of the type of (23) assumes that the characteristics of the random field U are known, and it is just these characteristics that define the model of a disordered system.…”
Section: The Localization Threshold Of Electronic States In the Lifshmentioning
confidence: 99%
“…The condition for the p_resence of bound states in the potential 7 is detll"K-'ll = 0. Because the matrix II"K-'II from (27) is diagonal, the presence of bound state with the given 1 is equivalent to (29) Assuming that both matrices (21) and (22) are considered in the energy region close to some eigenvalue of the Hamiltonian H,, excluding the eigenvalue itself. it may be concluded that the condition (29) is approximately satisfied.…”
Section: mentioning
confidence: 99%